(untitled) (Journal of the College of Basic Education, 2025)
This study aims to analyze the content of the physics textbooks for the first and second intermediate grades in Iraq for the academic year 2024–2025 in light of the dimensions of sustainable development. The researcher adopted the descriptive-analytical approach, relying on a content analysis tool developed after a comprehensive review of the principles of Education for Sustainable Development (ESD), relevant literature, and previous studies. The tool included three main dimensions: environmental, social, and economic—each comprising specific subdomains and detailed indicators. The environmental dimension covered three areas: conservation of natural resources (6 sub-indicators), reduction of air pollution and climate change (5 sub-indicators), and energy conservation (3 sub-indicators). The social dimension encompassed five areas: equality and social justice (4 indicators), health (6 indicators), education (6 indicators), housing and population (4 indicators), and safety and security (4 indicators). The economic dimension consisted of two areas: sustainable economic development (7 indicators) and responsible production and consumption patterns (5 indicators), bringing the total to 50 sub-indicators. The analysis was conducted systematically across all chapters of both textbooks. The first intermediate textbook comprised five chapters with 76 pages analyzed, while the second intermediate textbook included six chapters spanning 70 pages. The frequency of sustainable development concepts was recorded, and their proportional representation calculated. Findings revealed that the environmental dimension had the highest presence in both textbooks, accounting for 63% of the first intermediate textbook (24 occurrences) and 68% of the second intermediate textbook (37 occurrences). It was followed by the social dimension, which appeared at a rate of 31% in the first textbook (12 occurrences) and 16% in the second (9 occurrences). The economic dimension had the lowest representation, with 5% in the first textbook and 14% in the second.The study concludes with several recommendations, most notably the need to integrate sustainable development concepts more equitably across physics textbooks and to incorporate practical, real-world models that help students connect scientific concepts to their everyday lives—particularly in the context of current environmental and economic challenges.